2021
DOI: 10.1038/s41523-021-00264-2
|View full text |Cite
|
Sign up to set email alerts
|

NRG Oncology/NSABP B-47 menstrual history study: impact of adjuvant chemotherapy with and without trastuzumab

Abstract: The NRG Oncology/NSABP B-47 menstrual history (MH) study examined trastuzumab effects on menstrual status and associated circulating reproductive hormones. MH was evaluated by questions related to hysterectomy, oophorectomy, and reported menstrual changes. Pre/perimenopausal women were assessed at entry, 3, 6, 12, 18, 24, 30, and 36 months. Consenting women had estradiol and FSH measurement at entry, 3, 6, 12, 18, and 24 months. Logistic regression determined predictors of amenorrhea and hormone levels at 12, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It is possible that therapy-induced amenorrhea contributes to the benefit but it should be noted that many women with chemotherapy-induced amenorrhea continue to have premenopausal estradiol levels. 32 Therefore, direct antitumor effects of chemotherapy also likely contribute to the observed benefit. Qualifying statement: The genomic assay is prognostic and may be used for shared patient-physician treatment decision making.…”
Section: Characteristics Of Studies Identified In the Literature Searchmentioning
confidence: 99%
“…It is possible that therapy-induced amenorrhea contributes to the benefit but it should be noted that many women with chemotherapy-induced amenorrhea continue to have premenopausal estradiol levels. 32 Therefore, direct antitumor effects of chemotherapy also likely contribute to the observed benefit. Qualifying statement: The genomic assay is prognostic and may be used for shared patient-physician treatment decision making.…”
Section: Characteristics Of Studies Identified In the Literature Searchmentioning
confidence: 99%
“…The NSABP B-47 clinical trial showed that chemotherapy induced amenorrhea in pre-menopausal women is common but it is often discordant with hormone level measurements. In this study, 85% of patients were amenorrhoeic at 12 months after starting adjuvant chemotherapy but only 28 and 22% had postmenopausal estradiol levels at 12 and 24 months 11 . The SOFT and TEXT trials demonstrated that in premenopausal HR+ patients ovarian suppression plus an aromatase inhibitor is more effective than tamoxifen alone to improve recurrence-free survival 12 , 13 .…”
Section: Introductionmentioning
confidence: 52%
“…It is possible that therapy-induced amenorrhea contributes to the benefit but it should be noted that many women with CT-induced amenorrhea continue to have premenopausal estradiol levels. 10,11 Is the number of positive LN a determinant of which GES to use?…”
Section: Genomic Definition Of High Riskmentioning
confidence: 99%